2021
DOI: 10.1089/neu.2021.0071
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Cardiorespiratory Fitness, but Not Arterial Health, after Spinal Cord Injury: The CHOICES Trial

Abstract: Data availability statement:The CHOICES trial protocol and statistical analysis plan have been published. The datasets that were collected and analyzed for the purpose of this trial are available with de-identified participants data from the corresponding author upon reasonable request, subject to a standard data-sharing agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“… Ordonez et al (2013) and Rosety-Rodriguez et al (2014) , as well as Nightingale et al (2017b , 2018) reported different outcome measures from the same group of participants; the results from these corresponding studies by the same authors were combined and reported as a single study. Since the purpose of this review was to determine the effects of ACE in chronic SCI, studies comparing ACE with a different type of intervention [e.g., whole-body exercise ( Alrashidi et al, 2021 ), strength training ( Jacobs, 2009 ), functional electrical stimulation ( Farkas et al, 2021 )] or comparing SCI with non-injured adults ( El-Sayed and Younesian, 2005 ; Horiuchi and Okita, 2017 ) were treated as pre-post studies without a control group and only data from the ACE group were extracted. Three RCTs, one non-RCT, and thirteen pre-post studies were identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Ordonez et al (2013) and Rosety-Rodriguez et al (2014) , as well as Nightingale et al (2017b , 2018) reported different outcome measures from the same group of participants; the results from these corresponding studies by the same authors were combined and reported as a single study. Since the purpose of this review was to determine the effects of ACE in chronic SCI, studies comparing ACE with a different type of intervention [e.g., whole-body exercise ( Alrashidi et al, 2021 ), strength training ( Jacobs, 2009 ), functional electrical stimulation ( Farkas et al, 2021 )] or comparing SCI with non-injured adults ( El-Sayed and Younesian, 2005 ; Horiuchi and Okita, 2017 ) were treated as pre-post studies without a control group and only data from the ACE group were extracted. Three RCTs, one non-RCT, and thirteen pre-post studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Exercise intensity was commonly prescribed based on a percentage of peak oxygen consumption (V̇O 2peak ) (5/17), peak heart rate (for level of injury below T6; 3/17) or peak heart rate reserve (for level of injury above T6; 3/17), or using ratings of perceived exertion (e.g., Borg CR10 scale or Borg RPE 6-20 scale; 3/17). In addition, exercise intensity in each study was defined as either light, moderate, moderate-to-vigorous, or vigorous-intensity based on the classification of the American College of Sport Medicine ( Mitchell et al, 2019 ; American College of Sports, 2021 ) ( Table 3 ); one study used light-intensity ( Brizuela et al, 2020 ), three studies employed moderate-intensity ( McLean and Skinner, 1995 ; Dyson-Hudson et al, 2007 ; Farkas et al, 2021 ), nine applied moderate-to-vigorous-intensity ( Davis et al, 1987 ; DiCarlo, 1988 ; El-Sayed and Younesian, 2005 ; Ordonez et al, 2013 ; Horiuchi and Okita, 2017 ; Nightingale et al, 2017b ; Graham et al, 2019 ; Williams et al, 2020 ; Alrashidi et al, 2021 ), and four trained at vigorous-intensity ( Silva et al, 1998 ; Jacobs, 2009 ; Harnish et al, 2017 ; Bresnahan et al, 2019 ). Arm cranking speed was between 50 and 60 revolutions per minute.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations